Mineralogical and geochemical characterization of stream sediments to identify their rocks in the Buileso, Seleguju basin, Lolotoe Complex Bobonaro area (East Timor) - Silva, Albino da (2019)
Dissertação de Mestrado em Geociências apresentada à Faculdade de Ciências e Tecnologia